Single-cell transcriptomics reveals cellular dynamics and chemokine CXCL2-mediated smooth muscle cell proliferation in arterial repair - Huang, Xingxiao; Ping, Yan; Sun, Qiuli; Yu, Mingjun; Yang, Chao; Liu, Xiao; Wang, Long; Huang, Jinyu (Frontiers in Immunology, 2025)
BackgroundPercutaneous coronary intervention (PCI) remains the primary treatment for coronary artery disease (CAD), yet post-procedural arterial injury triggers cellular change and pathological inflammation, leading to thrombosis and restenosis. Recent studies have highlighted the chemokine CXCL2 play an important role in the immune response to tissue repair. However, the cellular mechanisms and the role of chemokine CXCL2 underlying arterial repair after PCI remain poorly understood.MethodsSingle-cell RNA sequencing (scRNA-seq) was used to characterize the heterogeneity and gene expression profiles of cells in a femoral artery injury (FAI) model. Animal models of FAI and cellular experiments were used to validate the effects of CXCL2 on smooth muscle cell proliferation.Results(1) Mesenchymal stem cells (MSCs), smooth muscle cells (SMCs), and macrophages play pivotal roles in arterial repair. And distinct subpopulations within these cell types were identified, each exhibiting unique functional characteristics and temporal dynamics during repair. (2) Notably, we identified an inflammatory SMC subpopulation (SMC2) that actively secretes chemokine CXCL2, which promotes SMC proliferation and mediates arterial remodeling after injury, suggesting its potential as a therapeutic target.ConclusionsThis study provides a comprehensive cell atlas of the injured artery, offering valuable insights into the complex cellular interactions, signaling pathways and immune responses involved in orchestrating vascular repair. Our findings show chemokine CXCL2 as a key mediator of SMC proliferation and provide a roadmap for developing CXCL2-targeted therapies to improve vascular outcomes in PCI patients.